Urban development interventions and living conditions in the informal settlement of Yaounde - Essounga, Angeline Raymonde Ngo; Achu, Frida Njiei (Technium Social Sciences Journal, 2021)
Since the mid-2000s, the political capital of Cameroon, Yaounde is undergoing construction with many urban development projects coordinated by the Yaounde City Council carried out in residential areas and informal settlements. These various activities as many other urban development projects have impacts on the living conditions of the inhabitants. This article focuses on the projects specifically carried out in the informal settlements, aims at analyzing the meaning and the scope of those projects in the lives of individuals and communities. Indeed, this work, is interested in the different operations of eviction, opening up and restructuring that took place in the informal settlements as well as their social consequences on the entire population of the city. It describes these different operations as public actions that are not deployed over the entire area occupied by the popular neighborhoods in Yaoundé, but only on certain slums concentrated around the central town. These results and conclusion are developed from data obtained during direct observations in the slums, from archives and from semi-structured interviews with some urban actors who participated in the implementation of urban development programs in the slums of Yaoundé.